2018
DOI: 10.1097/qai.0000000000001631
|View full text |Cite
|
Sign up to set email alerts
|

HIV Care Continuum Disparities Among Black Bisexual Men and the Mediating Effect of Psychosocial Comorbidities

Abstract: Black MSMW were less likely than black MSMO to uptake biomedical care and secondary prevention. Biobehavioral intervention development specific to HIV-positive black MSMW will be most successful if psychosocial comorbidities are also addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…There is also evidence that gay and bisexual men differ in other aspects of biomedical HIV prevention, although these studies have largely focused on MSMW rather than selfidentified bisexual men. Previous research has found that, compared to HIV-positive MSMO, HIV-positive MSMW are less likely to be aware of their HIV-positive status and to receive HIV care (Friedman et al, 2018), less likely to be virally suppressed Friedman et al, 2015), more likely to experience later HIV diagnoses (Singh et al, 2014), and more likely to receive an AIDS diagnosis within 1-3 years of initial HIV diagnosis (Singh et al, 2014). Further, there is some evidence that HIV care continuum outcomes are particularly disparate among both behaviorally and self-identified bisexual men (Friedman et al, 2018).…”
Section: The Movement Toward Biomedical Hiv Preventionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is also evidence that gay and bisexual men differ in other aspects of biomedical HIV prevention, although these studies have largely focused on MSMW rather than selfidentified bisexual men. Previous research has found that, compared to HIV-positive MSMO, HIV-positive MSMW are less likely to be aware of their HIV-positive status and to receive HIV care (Friedman et al, 2018), less likely to be virally suppressed Friedman et al, 2015), more likely to experience later HIV diagnoses (Singh et al, 2014), and more likely to receive an AIDS diagnosis within 1-3 years of initial HIV diagnosis (Singh et al, 2014). Further, there is some evidence that HIV care continuum outcomes are particularly disparate among both behaviorally and self-identified bisexual men (Friedman et al, 2018).…”
Section: The Movement Toward Biomedical Hiv Preventionmentioning
confidence: 98%
“…Of the few existing interventions, most focus on Black MSMW (with one exception focused on Hispanic/Latino MSMW) and are still in the early stages of efficacy testing (Fernandez et al, 2016;Harawa et al, 2018;Harawa et al, 2013;Lauby et al, 2018;Williams et al, 2013;Williams, Ramamurthi, Manago, & Harawa, 2009). Additionally, while biomedical advances are changing the field of HIV prevention, accumulating evidence suggests that they are not reaching bisexual men to the same extent as gay men Friedman et al, 2015;Friedman et al, 2018;Grov, Rendina, Jimenez, & Parsons, 2016). As such, in an effort to advance research on bisexual men and their sexual health needs, the goals of this commentary are to describe gaps in our understanding of sexual health among bisexual men and to discuss ways to address these gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Lower educational attainment is associated with lower income and lack of health insurance, which may promote sexual risk behaviors among MSMW at risk for HIV infection and inhibit treatment and care among MSMW with HIV infection [14,15]. Therefore, effective HIV prevention and care strategies and interventions for MSMW should consider educational attainment [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…From 2014-2017, POWER utilized time-location sampling (TLS) to recruit a large sample of BMSM at Black Pride events in six U.S. cities: Atlanta, GA; Detroit, MI; Houston, TX; Memphis, TN; Philadelphia, PA; and Washington, DC (Friedman et al, 2018). In each city, recruitment events were randomly selected in two-hour time blocks from all official Black Pride events.…”
Section: Methodsmentioning
confidence: 99%
“…Participants received $10 for completion of the survey and $10 for completion of HIV testing. HIV test results were anonymously linked to survey files via a unique subject ID (Friedman et al, 2018). All study procedures were approved by the Institutional Review Board at the University of Pittsburgh.…”
Section: Methodsmentioning
confidence: 99%